PURIFIKASI DAN KARAKTERISASI ENZIM PEKTINASE DARI ASPERGILLUS USTUS BL5 - Yopi, Yopi; Rahmani, Nanik; Andriani, Ade; Dewi, Fitria; Meryandini, Anja (BERITA BIOLOGI, 2013)
Pectinase is an enzyme that could hydrolyze pectin into galacturonic acid. Natural pectinase was produced by microbes such as bacteria, yeast, fungi and Actinomycetes. Application of pectinase in industry were mainly in juice industry, textile, pulp, tea, cocoa and coffee fermentation. In this research, we conducted purification and characterization of pectinase produced by Aspergillus ustus BL5 in submerged fermentation using commercial pectin. The result showed that the optimum of pectinase production was reached at 120 hours fermentation process with specific activity 0.59 U/mg. The crude extract of pectinase was then concentrated using PEG 6000 and purified by Sephadex G-75 gel filtration chromatography. There were 2 fractions contained pectinase which the activity was 4.15 U/mg (pectinase A) and 3.3 U/mg (pectinase B), respectively. Compare to crude extract, the yield product of pectinase A and B increased 6.94 and 5.53 times, respectively. The purified pectinase A have optimum temperature at 50 oC and optimun pH at 5.